A general FDTD algorithm handling thin hybrid dispersive layers - Yun Zhou; Bing Wei; Peng Yin (2011 IEEE International Conference on Microwave Technology and Computational Electromagnetics, 2011)
A novel general technique for treating electrically thin hybrid dispersive layer with the finite difference time domain (FDTD) method is introduced. The proposed model is based on the modifying of the node update equations to account for the layer, where the electric flux densities are locally averaged in the FDTD grid. Then, based on the characteristics of hybrid models, the permittivity can be formulated by rational polynomial fraction in j ω. The conversion equation from frequency-domain to time-domain and the shift operator method are then applied to obtain the constitutive relation at modified electrical points and the time-domain recursive formula for D and E. A numerical example is presented and they are in good agreement with the one obtained by analytic method. This illustrates the generalization and the feasibility of the presented scheme.